Optimization of Indonesian Youth Knowledge In Stunting Prevention Assistance - Novita, Sely; Taryana, Amalia Marjan; Setyowati, Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The prevalence rate of stunting in Indonesia in 2021 reached 24.4%, surpassing the WHO standard of 20%. As a result, Indonesia is categorized as having a high stunting issue and holds the 2nd position in Asia. Efforts to reduce stunting are closely related to the role of health cadres. Indonesian youth play a crucial role as agents of change, having a 39.8% influence in community involvement. Kader Muda Sehat training, as an innovative program, aims to train young individuals to become health cadres, enabling them to contribute in assisting the targeted individuals affected by stunting.The objective of this study is to analyze the effectiveness of the Kader Muda Sehat training program in enhancing the knowledge of youths as health cadres in the Banyuresmi Subdistrict, Garut Regency. This study was conducted using a quasi-experimental approach with one-group pre-test-post-test design. Kader Muda Sehat training was conducted over 7 sessions from December 2022 to January 2023, using a hybrid approach, online through Zoom meetings and offline in the Karyasari Village, Banyuresmi Subdistrict, Garut Regency, West Java. The sampling technique used in this study was purposive sampling, consisting of 18 young cadres who met the established inclusion criteria. Data collection of young cadre characteristics and knowledge was carried out using pre-test-post-test questionnaires. The research data were analyzed using univariate and bivariate, specifically the related samples Wilcoxon signed-rank test, utilizing SPSS Statistics V25.0 software. The results showed a p-value of 0.000 (0.000 < 0.05), indicating a positive influence of Kader Muda Sehat training on the level of knowledge of young cadres regarding stunting prevention assistance. Based on results, it was concluded that there was an improvement in the youths' knowledge after receiving Kader Muda Sehat training about stunting prevention assistance. Kader Muda Sehat training is effective in enhancing youths' knowledge of stunting prevention assistance.